ANALISIS KASUS KEKERASAN OLEH GURU DI LINGKUNGAN PENDIDIKAN SEKOLAH: PERSPEKTIF PROFESIONALISME DAN ETIKA - Permatasari, Faudina; Azzahro, Siti Nurdyana (Jurnal Dedikasi Pendidikan, 2025)
Violence committed by teachers in schools reflects a serious violation of the ethical standards and professional guidelines that should govern education. This study examines five cases of physical violence by educators in various schools across Indonesia, encompassing verbal, physical, and sexual abuse. The purpose of this research is to identify patterns, causes, and the impact of such violence on students, both physically and psychologically. The research employs a descriptive qualitative method with a case study and literature review approach. The findings reveal that violence is triggered by teachers' inability to manage their emotions, improper disciplinary methods, and a lack of supervision in schools. To prevent such incidents, teacher training, consistent implementation of ethical codes, and stricter oversight of teacher qualifications are necessary.